Invasive pneumococcal disease: From a tertiary care hospital in the post-vaccine era. Issue 4 (3rd April 2017) - Tanır Basaranoglu, Sevgen; Karadag Oncel, Eda; Aykac, Kubra; Ozsurekci, Yasemin; Cengiz, Ali Bülent; Kara, Ates; Ceyhan, Mehmet
ABSTRACT: A breakthrough infection occurring with 13-valent pneumococcal conjugate vaccine (PCV13) in Turkey are previously described. A breakthrough infection is defined as IPD in a child who had received ≥ 1 PCV-7 or PCV-13 and for which the pneumococcal isolate was a vaccine serotype. During one year period, among 6 patients with invasive pneumococcal infection, 2 patients were considered to have a vaccine failure with serotype 19F. Antibiotic resistance results were remarkable; macrolide resistance were observed in all strains except one, and high and intermediate penicillin resistance were determined in 2 strains.